Analisis Efektivitas dan Kontribusi BPHTB dan PBB-P2 Terhadap PAD Kota Bekasi 2019-2024 - Adinda Zahra Fadila; Tresno Eka Jaya; Septi Nurmalita (LPPM Universitas Negeri Jakarta, 2026)
This study analyzes the effectiveness and contribution of Land and Building Acquisition Duty (BPHTB) and Rural and Urban Land and Building Tax (PBB-P2) revenues to the Regional Original Revenue (PAD) of Bekasi City for the 2019-2024 period, and formulates optimization strategies through SWOT analysis. The data used are primary data from in-depth interviews with Bapenda officials, notaries/PPAT, taxpayers, and tax consultants, and secondary data on tax revenue targets and realizations. This study uses a descriptive method with a mixed-methods approach, combining effectiveness and contribution ratio analysis with qualitative SWOT analysis. The results show that: (1) BPHTB effectiveness averaged 99 percent (effective), while PBB-P2 effectiveness averaged 81 percent (fairly effective); (2) BPHTB contribution to PAD averaged 20 percent (moderate) and PBB-P2 contribution averaged 18 percent (poor); and (3) recommended strategies include optimizing tax digitalization, updating tax object data, strengthening inter-agency coordination, and improving taxpayer education and service accessibility.